2022
DOI: 10.1186/s13287-022-03153-y
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord blood mononuclear cells transplantation for perinatal brain injury

Abstract: Perinatal brain injury is a leading cause of death and disability in children. Hypoxic-ischemic encephalopathy in full term infants, and white matter injury in premature infants are most known brain injury in perinatal period. Human umbilical cord blood mononuclear cells contain hematopoietic stem cells, mesenchymal stem cells, endothelial progenitor cells, lymphocytes, monocytes, and so on. Human umbilical cord blood mononuclear cells have many biological functions, such as nerve and vascular regeneration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…These cells can modulate the immune response and reduce inflammation, which are important factors in intimal hyperplasia development, 17 and it may promote vascular repair and inhibit the development of intimal hyperplasia. 18 The combination of umbilical cord mesenchymal stem cells and HIF-1α can enhance these angiogenic properties and improve the outcomes of arteriovenous fistula creation. Zhang et al conducted a study that found human umbilical cord mesenchymal stem cells produced exosomes promote angiogenesis through HIF-1α, which is beneficial to fracture healing.…”
Section: Level Of Hif-1αmentioning
confidence: 99%
“…These cells can modulate the immune response and reduce inflammation, which are important factors in intimal hyperplasia development, 17 and it may promote vascular repair and inhibit the development of intimal hyperplasia. 18 The combination of umbilical cord mesenchymal stem cells and HIF-1α can enhance these angiogenic properties and improve the outcomes of arteriovenous fistula creation. Zhang et al conducted a study that found human umbilical cord mesenchymal stem cells produced exosomes promote angiogenesis through HIF-1α, which is beneficial to fracture healing.…”
Section: Level Of Hif-1αmentioning
confidence: 99%
“…UCB refers to blood within the umbilical cord and blood vessels surrounding the fetal component of the placenta. [17] Numerous cell types comprise UCB including HSCs, MSCs, Tregs, monocytes and EPCs. [81] In our review, all four outcomes which demonstrated statistically significant differences between UCB cell types were associated with a favoured modification of treatment effect in MSCs over MNCs.…”
Section: Ucb Cell Typementioning
confidence: 99%
“…[9,[13][14][15] Umbilical cord blood (UCB)-derived cell therapy is one of the most prominent emerging interventions in this area of research and has received a large amount of attention in both preclinical and clinical studies. [16][17][18][19] In part A of this review, we demonstrated UCB-derived cells (UCBCs) were effective in improving both neuropathological and behavioural outcomes in preclinical models. The specific outcomes investigated were apoptosis, astrogliosis, infarct size, microglial activation, oligodendrocyte number, neuroinflammation and motor function.…”
Section: Introductionmentioning
confidence: 99%
“…Human umbilical cord blood mononuclear cells, which are isolated from the umbilical cord blood of pregnant women after delivery, are mononuclear cells and the largest cells in the human body; these cells include a variety of stem cells, lymphocytes and monocytes 14 . HUCB-MNCs have a variety of biological functions, such as tissue and cell regeneration, anti-inflammatory effects, and immune regulation 14 . Umbilical cord blood mononuclear cells can differentiate into a variety of immune cells as needed and can expand into a large number of highly active immune cells in vitro.…”
Section: Introductionmentioning
confidence: 99%